-5x+4(-3+3)=-192

Simple and best practice solution for -5x+4(-3+3)=-192 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+4(-3+3)=-192 equation:


-5x+4(-3+3)=-192

We simplify the equation to the form, which is simple to understand
-5x+4(-3+3)=-192

Simplifying terms in parentheses
-5x+4*()=-192

Reorder the terms in parentheses
-5x+()=-192

Remove unnecessary parentheses
-5x0=-192

We move all terms containing x to the left and all other terms to the right.
-5x=-192-0

We simplify left and right side of the equation.
-5x=-192

We divide both sides of the equation by -5 to get x.
x=38.4

See similar equations:

| x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 | | x=.4+(-.2y) | | B-2+6B=27 | | 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 | | 7x+15=29 | | 7a+21b=35 |

Equations solver categories